Kesalahan Konseptual dan Prosedural Mahasiswa Calon Guru Matematika dalam Menyelesaikan Soal Non-Rutin pada Topik Pencerminan - Umar, Ali (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2025)
Conceptual and procedural errors are still frequently found among prospective mathematics teachers when solving mathematical problems. However, the questions commonly used to assess conceptual and procedural understanding tend to be routine in nature, which may not adequately reflect students’ mastery of the material. Therefore, this study aims to analyze the conceptual and procedural errors made by prospective mathematics teachers when solving a non-routine problem related to the topic of reflection. This research employed a qualitative descriptive approach, involving 16 students from the Mathematics Education program at UIN Mahmud Yunus Batusangkar. The research instrument consisted of a single non-routine problem administered after the students had studied the topic of reflection. The results showed that 11 students were able to solve the problem correctly, while the remaining 5 made errors. The identified conceptual errors included a lack of understanding of the concepts of reflection and linear equations, as well as incorrect use of mathematical notation. Procedural errors involved computational mistakes and carelessness in forming equations. These findings indicate that strengthening students' conceptual and procedural understanding is still necessary before directing them toward developing higher-order thinking skills.